Diagnostic accuracy of copeptin sensitivity and specificity in patients with suspected non-ST-elevation myocardial infarction with troponin I below the 99th centile at presentation. Issue 3 (24th March 2014) - Duchenne, Jonathan; Mestres, Stéphanie; Dublanchet, Nicolas; Combaret, Nicolas; Marceau, Geoffroy; Caumon, Laurent; Dutoit, Laurent; Ughetto, Sylvie; Motreff, Pascal; Sapin, Vincent; Schmidt, Jeannot
Abstract : Objective: To determine whether copeptin-us can rule out diagnosis of non-ST-segment elevation myocardial infarction (NSTEMI) without prolonged monitoring and serial blood sampling in patients with high-sensitive cardiac troponin I (hs-cTnT) below the 99th centile at presentation to the emergency department (ED). Design: Prospective, non-randomised, individual blinded diagnostic accuracy study. Setting: Two EDs of a rural region of France. Participants: Patients with chest pain suspected of NSTEMI with onset within the last 12 h were considered for enrolment. Interventions: Serial clinical, electrographical and biochemical investigations were performed at admission and after 2, 4, 6 and 12 h. Hs-cTnT was measured using an assay with Dimension VISTA, Siemens. Copeptin was measured by the BRAHMS copeptin-us assay on the KRYPTOR Compact Plus system. The follow-up period was 90 days. Primary and secondary outcome measures: Copeptin, troponin, myoglobin and creatine kinase values. Clinical and paraclinical events. The final diagnosis was adjudicated blinded to copeptin result. Results: During 12 months, 102 patients were analysed. Final diagnosis was NSTEMI for 7.8% (n=8), unstable angina for 3.9% (n=4), cardiac but non-coronary artery disease for 8.8% (n=9), non-cardiac chest pain for 52% (n=53) and unknown for 27.5% (n=28). There was no statistical difference for copeptin values between patients with NSTEMI and others (respectively 5.5 pmol/L IQR (3.1–7.9) and 6.5 pmol/L IQR (3.9–12.1), p=0.49). Only one patient with NSTEMI had a copeptin value above the cut-off of 95th centile at admission. Conclusions: In this study, copeptin does not add a diagnostic value at admission to ED for patients with suspected acute coronary syndrome without ST-segment elevation and with hs-cTnT below the 99th centile. Trial registration number: Clinicaltrials.gov identifier: NCT01334645 .